An Indicators of Return on Equity and Development of its Analysis - Mackevičius, Jonas; Poškaitė, Dalia (Ekonomika, 1999)
The basic concept of return on equity (ROE) is relatively simple to understand. However, care must be used in determining the elements entering its computation because there exists a variaty of views, which reflect different objectives of how these elements should be used in computation of return on equity ratios. The article aims to reveal the discussion of computation and to rise analitical problems of return on equity. The analysis of return on equity is complex process requiring thorough examining factors, which influence this ratio.The article also is devoted to development of methodical problems of return on equity.